Early Child Development in China : Breaking the Cycle of Poverty and Improving Future Competitiveness - Wu, Kin Bing (Washington, DC: World Bank, 2012)
In the past 30 years, China has reached the target of lifting 500 million people out of poverty. The rate of increase in human development indicators has become the second fastest in the world, allowing China to enter the ranks of middle-income countries. As the most populous country, accounting for one-fifth of the world's population, its transformation has been unprecedented in human history. Scientific evidence and international experience in the past 10 years have found that early child development (ECD) is key to human development, as it lays the foundation for the rest of life. Early child development includes physical, psychological, emotional, language, behavioral, and social development. Experience in the early years of life will determine healthy development and happiness in the rest of life. Research has found that investment in ECD is the most cost effective strategy to improve human development. In China's demographic transition, the population of children and youth is declining in absolute numbers, and the investment of raising them can increase on a per capita basis. This study has been in the making since 2009. It was prepared during a time when China was charting its course of development under the 12th Five-Year Plan (2011-2015). The study began with an agreement between the World Bank and China's National Population and Family Planning Commission (NPFPC) for a collaborative study on ECD. Concurrently, China's Ministry of Education invited the World Bank to conduct an overall review of the education sector, in order to provide it with inputs and suggestions as it prepared China's national plan for medium- and long-term education reform and development (2010-2020). In reviewing achievements and challenges in the education sector, the Bank found that there was much room for expanding and improving preprimary education for children ages 3-6. The Ministry of Education appreciated the Bank's identification of this need and set ambitious goals for preprimary education in the national education plan.